Relationship between serum inflammatory markers and recurrent atrial fibrillation in patients undergoing pulmonary vein isolation - E. N. Tsareva; K. V. Davtyan; A. G. Topchyan; M. S. Kharlap; A. A. Kalemberg; А. A. Brutyan; I. A. Efimova; N. L. Bogdanova (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To study the baseline level of inflammatory markers (IM) and proteins of serum proteolytic system in patients scheduled for pulmonary vein isolation, and to analyze the potential of IM to predict the arrhythmogenic foci outside the PV sleeves — non-pulmonary vein dependent atrial fibrillation (AF).Material and methods. The study included 100 patients with paroxysmal (n=89) and persistent (n=11) AF who underwent the primary PV cryoballoon ablation with the simultaneous implantation of a loop recorder (Reveal XT, Medtronic). Before the procedure, we analyzed following parameters in all patients: N-terminal pro-brain natriuretic peptide (NTproBNP), matrix metalloproteinases 1, 3, 9, tissue inhibitor of matrix metalloproteinase 1, fibroblast growth factor-2, fatty acid binding protein 3, transforming growth factor p1, tumor necrosis factor a, interleukin 1p.Results. A significant negative predictive value of baseline NTproBNP (hazard ratio, 1,00053, p=0,00935) for recurrent AF (recurrence risk increases by 8,4% with an increase in NTproBNP level by 100 pg/ml) was demonstrated. For the rest of the parameters, there was no significant effect on recurrence risk in the postoperative period.Conclusion. The role of IM in the AF pathogenesis should be studied further, taking into account the recommended sample sizes to assess their predictive ability in relation to preoperative detection of patients with non-pulmonary vein dependent.